Preschoolers' performance on the brazilian adaptation of the preschool language assessment instrument - Second edition - Lindau, Tâmara Andrade [UNESP]; Rossi, Natalia Freitas [UNESP]; Giacheti, Celia Maria [UNESP] (Karger Publishers, 2016)
Purpose: The objective was to test whether the Brazilian version of the Preschool Language Assessment Instrument - Second Edition (PLAI-2) has the potential to assess and identify differences in typical language development of Portuguese-speaking preschoolers. Methods: The study included 354 children of both genders with typical language development who were between the ages of 3 years and 5 years 11 months. The version of the PLAI-2 previously translated into Brazilian Portuguese was used to assess the communication skills of these preschool-age children. Results: Statistically significant differences were found between the age groups, and the raw score tended to increase as a function of age. With nonstandardized assessments, the performances of the younger groups revealed behavioral profiles (e.g., nonresponsive, impulsive behavior) that directly influenced the evaluation. Conclusions: The findings of this study show that the PLAI-2 is effective in identifying differences in language development among Brazilian children of preschool age. Future research should include studies validating and standardizing these findings.
Keywords: Assessment; Child; Language; Language tests; Preschool; Speech-language pathology